Ultimate capacity and failure mechanism of SCS and S-UHPC composite deep beams: Test and modeling. (15th October 2021) - Lin, Youzhu; Yan, Jiachuan; Wang, Zefang; Fan, Feng; Zou, Chaoying
Highlights: Eight SCS and S-UHPC deep beams under static loads are tested. Effects of shear span ratio, concrete type and shear stud spacing are explored. Failure mechanism of specimens is analyzed by a modified Strut-and-Tie model. A slip coefficient is deduced to design the shear connectors reasonably. Theoretical models of ultimate capacity with different failure modes are proposed. Abstract: In this study, a type of steel–concrete–steel (SCS) composite deep beam with ultra-high-performance concrete, named S-UHPC deep beam, was developed. Eight simply supported deep beams, including three SCS deep beams and five S-UHPC deep beams, were tested under static loads. The effects of different parameters (including the shear span ratio, concrete type, and shear stud spacing) on the ultimate capacity, ductility, and interfacial slip of the specimens were explored. Moreover, the observed failure modes were categorized into shear failure without slip, slip failure, and flexural failure with the snapping of steel fibers. To analyze the failure mechanism systematically, finite element (FE) models of the specimens were established and validated. By analyzing the FE simulation results on the compressive damage and stress distribution of the filled concrete, the von Mises stress distribution of shear studs, and the equivalent plastic strain distribution of the bottom steel faceplate, the failure mechanism of the specimens with the observed failure modes was simplified as a modified Strut-and-Tie model. Based on the force transfer analysis of the modified Strut-and-Tie model, a slip coefficient was deduced to quantify the composite action and provide theoretical supports for the reasonable design of shear connectors. Theoretical models of SCS deep beams and S-UHPC deep beams with different failure modes were presented to predict the ultimate capacity.